A Culture of Success–Examining School Culture and Student Outcomes via a Performance Framework - Ohlson, Matthew; Swanson, Anne; Adams-Manning, Andrea; Byrd, Anna (Journal of Education and Learning, 2016)
This study is a report of the relationship between a collaborative school culture, teacher quality and the influence these variables have upon student attendance and suspensions. The research is based upon data gathered from 50 public schools throughout the southeastern United States. Surveys were administered to examine teacher quality characteristics, elements of educational leadership, and components of a collaborative school culture. Data were analyzed in relation to teacher input characteristics such as certification, years teaching, percentage teaching out of field, and highest degree obtained. The findings revealed that as teacher collaboration increased, the model predicted that student suspensions would decrease by 6.709%. In addition, the model predicted that when the percentage of out-of-field teachers within a school increased, student suspensions would decrease by 0.16%. Finally, as the percentage of non-certified teachers within a school increased, the student suspension percentage increased by 0.22%. The findings offer valuable insight into the characteristics of quality teaching and school culture that demonstrate the greatest impact on student attendance and suspensions and may influence educational policy, teacher training, educational leadership, and school reform initiatives.
Keywords: Attendance; Correlation; Instructional Leadership; Multiple Regression Analysis; Public Schools; School Culture; School Surveys; Statistical Analysis; Suspension; Teacher Characteristics; Teacher Effectiveness